2020
DOI: 10.1371/journal.pone.0240645
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Positive Airway Pressure (CPAP) face-mask ventilation is an easy and cheap option to manage a massive influx of patients presenting acute respiratory failure during the SARS-CoV-2 outbreak: A retrospective cohort study

Abstract: Positive Airway Pressure (CPAP) face-mask ventilation is an easy and cheap option to manage a massive influx of patients presenting acute respiratory failure during the SARS-CoV-2 outbreak: A retrospective cohort study. PLoS ONE 15(10): e0240645.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 45 publications
1
53
1
2
Order By: Relevance
“…In general, the studies have shown that the treatment with CPAP was well tolerated with few patients dropping out. Still, the intubation rate was high between 42% and 57% [ 7 , 8 , 10 , 12 ] among those without a ceiling of treatment in the ward and comparable to our study. Only one study had 83% recovering from CPAP treatment alone [ 11 ].…”
Section: Discussionsupporting
confidence: 90%
“…In general, the studies have shown that the treatment with CPAP was well tolerated with few patients dropping out. Still, the intubation rate was high between 42% and 57% [ 7 , 8 , 10 , 12 ] among those without a ceiling of treatment in the ward and comparable to our study. Only one study had 83% recovering from CPAP treatment alone [ 11 ].…”
Section: Discussionsupporting
confidence: 90%
“…Recent experience in COVID-19 related Acute respiratory failure (21 publications including 1553 patients) 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 with HFNC, CPAP and Bi-Level Ventilation (using negative pressure rooms in only one series 15 ) shows average success of 60%, 55% and 59%, respectively, and an average infection rate in health professionals of 5.2%, less than the 12% reported in New York City among the staff not necessarily working with NIRT. 28 …”
mentioning
confidence: 99%
“…Some experiences conducted in the first phase of the epidemic in Europe in the operational context of the Emergency Department (ED) have described a situation characterized by an exponential growth of admitted patients and the urgent need to make more beds available in the ICU, coupled with their rapid occupation [10][11][12]. Criteria for initiating CPAP or non-invasive positive pressure ventilation (NPPV) in the various studies were a PaO2 of less than 60 mmHg or an oxygen saturation lower than 90-94% and or a respiratory rate greater than 25 per minute and signs of respiratory distress after application of non-rebreathing mask.…”
Section: The Outbreak Of the Pandemicmentioning
confidence: 99%